2021
DOI: 10.1016/j.ejro.2021.100335
|View full text |Cite
|
Sign up to set email alerts
|

Mitral annular disjunction in patients with severe aortic stenosis: Extent and reproducibility of measurements with computed tomography

Abstract: Highlights Mitral annulus disjunction (MAD) is frequent in patients with severe aortic stenosis. Computed tomography enables a highly reproducible assessment of MAD. MAD patients significantly more often have mitral valve prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…15 Another study of patients with severe aortic stenosis found MAD, in comparison to no MAD, was not associated with atrial flutter or fibrillation (34% vs 21%, p = 0.12, bundle branch block conduction (13% vs 26%, p = 0.13), atrioventricular block (19% vs 17%, p = 0.81) or permanent pacemaker implantation (0% vs 6%, p = 0.39) pre TAVI. 18 In one study, there was an association between the presence of ventricular arrhythmias (including symptomatic and frequent pre- 17 Here, CMR was able to detect MAD of smaller distances more frequently than TTE and TOE. 17 This review highlights that there is no consistent definition for clinically relevant MAD.…”
Section: Mad and Arrhythmic Eventsmentioning
confidence: 99%
See 4 more Smart Citations
“…15 Another study of patients with severe aortic stenosis found MAD, in comparison to no MAD, was not associated with atrial flutter or fibrillation (34% vs 21%, p = 0.12, bundle branch block conduction (13% vs 26%, p = 0.13), atrioventricular block (19% vs 17%, p = 0.81) or permanent pacemaker implantation (0% vs 6%, p = 0.39) pre TAVI. 18 In one study, there was an association between the presence of ventricular arrhythmias (including symptomatic and frequent pre- 17 Here, CMR was able to detect MAD of smaller distances more frequently than TTE and TOE. 17 This review highlights that there is no consistent definition for clinically relevant MAD.…”
Section: Mad and Arrhythmic Eventsmentioning
confidence: 99%
“…Our search yielded 80 potentially relevant studies. After screening of titles, abstracts, and full manuscripts of potentially relevant studies, a total of twelve studies 1,8,[11][12][13][14][15][16][17][18][19][20] met the inclusion criteria and were included in the review (Figure 4). 1.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations